2020
DOI: 10.1029/2020jd032929
|View full text |Cite
|
Sign up to set email alerts
|

Stratospheric Ozone in the Last Glacial Maximum

Abstract: Using the Whole Atmosphere Community Climate Model version 6, stratospheric ozone in the Last Glacial Maximum (LGM) is investigated. It is shown that, compared with preindustrial (PI) times, LGM modeled stratospheric temperatures are increased by up to 8 K, leading to faster ozone destruction rates for gas phase reactions, especially via the Chapman mechanism. On the other hand, stratospheric hydroxyl radical (OH) and nitrogen oxides (NO x) concentrations are decreased by 10-20%, which decreases catalytic ozon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
50
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(59 citation statements)
references
References 55 publications
8
50
1
Order By: Relevance
“…The latter is supported by satellite observations [15,16]. Fu et al [5] and Wang et al [17] used the Whole Atmosphere Community Climate Model version 6 (WACCM6) [18] to examine the BDC and stratospheric O 3 during the LGM. They showed that the stratospheric O 3 changes in the LGM as compared to the preindustrial climate were caused by chemical processes in the upper stratosphere associated with a temperature increase and OH and NO x decreases, a slow-down of the BDC in the lower stratosphere, and a lowering of the tropopause in the extratropics [17].…”
Section: Introductionmentioning
confidence: 91%
See 4 more Smart Citations
“…The latter is supported by satellite observations [15,16]. Fu et al [5] and Wang et al [17] used the Whole Atmosphere Community Climate Model version 6 (WACCM6) [18] to examine the BDC and stratospheric O 3 during the LGM. They showed that the stratospheric O 3 changes in the LGM as compared to the preindustrial climate were caused by chemical processes in the upper stratosphere associated with a temperature increase and OH and NO x decreases, a slow-down of the BDC in the lower stratosphere, and a lowering of the tropopause in the extratropics [17].…”
Section: Introductionmentioning
confidence: 91%
“…The WACCM6 has a realistic, internally generated QBO in the stratosphere and simulates a realistic frequency of SSWs [18,39]. We analyzed five simulations from Fu et al [5] and Wang et al [17], who used the WACCM6 with a horizontal resolution of 0.9 • latitude and 1.25 • longitude and 70 vertical levels. They consist of (1) a LGM simulation with prescribed SSTs based on models (LGM PMIP3 ), (2) a LGM simulation with SSTs based on proxy data (LGM PROXY ), (3) a preindustrial climate simulation (PI), (4) a modern climate simulation (MC), and (5) a modern climate simulation without ozone-depleting substances (ODS) (MC no_ODS ).…”
Section: Model Experimentsmentioning
confidence: 99%
See 3 more Smart Citations